The likelihood of a significant trend based on a family of Mann-Kendall tests for extreme rainfall in Borneo - Sa’adi, Zulfaqar; Samikan Mazilamani, Lelavathy; Sa’adi, Nurzalikha; Basri, Mohd Hadi Akbar; Alias, Nor Eliza; Yusop, Zulkifli; Zainon Noor, Zainura; Kemarau, Ricky; Shiru, Mohammed Sanusi; Masood, Andleeb (Elsevier, 2025)
Due to its ecological diversity, the island of Borneo is particularly vulnerable to the impacts of climate change. Positioned at the centre of the Maritime Continent, Borneo was the focus of this study, which thoroughly investigated the spatiotemporal trends of extreme rainfall across the region. By utilising the Expert Team on Climate Change Detection and Indices (ETCCDI) extreme rainfall indices, the study introduced a novel threshold-based likelihood classification to enhance the assessment of Mann-Kendall trend tests, enabling clearer identification of spatiotemporal patterns and providing practical guidance for risk assessment and decision-making. The Climate Hazards Group InfraRed Precipitation with Station (CHIRPS) daily rainfall dataset (1981–2022), covering 943 grid points, was used for this purpose. The results shoed that Borneo is expected to face a high-likelihood increase in extreme rainfall frequency ranging from 34.6 % to 52.6 %, with the central mountainous region experiencing the highest rise of 52.6 %. The affected areas are expected to expand southward and eastward, notably impacting southern Borneo (up to 36 grids) and East Kalimantan's eastern coast (up to 7 grids), with increases also observed in coastal-northern Sarawak, Brunei, and northwestern Sabah. These findings demonstrate the added value of combining multiple Mann-Kendall test variants with a likelihood framework to strengthen confidence in trend detection and effectively identify hotspots like southern Borneo and East Kalimantan's eastern coast. These results provide local governments, disaster management agencies, environmental planners, and water resource managers with a stronger scientific basis to develop targeted adaptation strategies and mitigate climate change impacts in Borneo.